Soil Chemical properties and Growth of Agarwood as an Intercropping in Palm Oil Land Plantations that Applied EFBPO Compost and Biochar: Sifat Kimia Ultisol dan Pertumbuhan Gaharu sebagai Intercropping di Lahan Kelapa Sawit yang Diaplikasikan Kompos dan Biochar TKKS - Vema Rohmawati Khasanah; Nelvia Nelvia; Wawan Wawan (JURNAL AGRONOMI TANAMAN TROPIKA (JUATIKA), 2020)
The aim of this research was to studied the nature of soil chemistry and growth of agarwood (Aquilaria malaccensis) as an intercropping plant in palm oil land plantations that applied EFBPO compost and biochar. The study was conducted in Bukit Kemuning from May 2018 to December 2019. This study used randomized block design. The treatment is applied EFBPO compost and biochar with 7 levels, namely : without EFBPO compost and biochar, gived 0.5 kg EFBPO compost per a plant, gived 0.5 kg EFBPO biochar per a plant, mixed at dose 0.25 kg EFBPO compost and 0.25 kg EFBPO biochar per a plant, gived 1 kg EFBPO compost per a plant, gived 1 kg EFBPO biochar per a plant, mixed at dose 0.5 kg EFBPO compost and 0.5 kg EFBPO biochar per a plant. Each treetment was repeated 3 times. The observed parameters were soil chemical properties, chlorophyll content, plant height, number of branches, diameter of the stem and leaf area. The results showed that the provision of EFBPO compost or biochar at dose of 0.5 kg or 1 kg per a plant and mixed both at a dose of 0.25 kg and 0.25 kg or 0.5 kg and 0.5 kg per a plant to increase Organic C, P total, K total, KTK and decrease Al dd each 61.83%-102%, 17.18%, 28.04%-64.09%, 23.98% and 14.29%-57.14% compared to control. It also increases plant growth, such as increases plant height, number of branches, diameter of the stem, and leaf area, each 0.67%-56.72%, 5.50%-22.17%, 7.69%-52.88% and 5.73%-125% compared to control.